Are Health Caregivers safe from workplace violence? A cross sectional study on workplace safety from Tertiary Care Hospital of Uttarakhand - Vyas, Shaili; Saini, Ravinder Singh; Semwal, Jayanti; Sharma, Neha; Chaturvedi, Manish; Ansari, Mohd. Waseem Faraz (Indian Journal of Community Health, 2022)
Background: The prevalence of workplace violence in the healthcare sector is a problem that is frequently ignored and underreported. The performance of healthcare workers who have been the target of violence may suffer, which may have a negative effect on patient satisfaction and health. Aims & Objectives: The purpose of the current study was to determine the prevalence of workplace violence (WPV), risk factors for violence against healthcare workers, and their experiences regarding the same. Methodology: It was a cross-sectional study conducted on 157 hospital staff at Tertiary Care Medical College of Uttarakhand. Data was gathered using a semi-structured, self-administered questionnaire that was modified from the ILO, ICN, WHO, and PSI. Data were analyzed using SPSS software (version 20). Results: Factors like age, gender, job profile, lesser work experience, night shifts, and fewer staff on duty were found to have a positive association with workplace violence. It was observed that the majority of incidents took place in the ward, and the patient’s relatives were the attacker in most of the cases. It was also seen that the majority of Hospital staff did not get bothered by the incident except by staying super alert while dealing with other patients or their relatives. Conclusion: The study concludes that while caring for patients, Hospital staff are at risk of being victims of aggressive and violent situations. To reduce this problem, strategies like training staff in order to handle such incidents in the future should be brought into practice. Laws should be made stricter & assaulting staff on duty should be made a cognizable offense with serious consequences & heavy penalties. Also, the young budding MBBS students should be trained by incorporating these strategies, laws & policies in the CBME curriculum